Sistem Monitoring Online dan Analisa Performansi PLTS Rooftop Terhubung ke Grid PLN - Habib Satria; Syafii Syafii (Jurnal Rekayasa Elektrika, 2018)
This paper presents an online monitoring system and PV system performance analysis under various weather conditions. The PV monitoring system consists of an Arduino sensors circuit, and a design monitor display built using Visual Basic.Net programming. The monitoring system was applied to the 1.25 kW PV system mounted on the roof of the Department of Electrical Engineering, Andalas University. The rooftop PV system is connected to the PLN grid using five units of 250 Wp polycrystalline solar panels and mounted flat in series connected to the load through a 2 kW grid tie inverter. The process of data retrieval of the results of the monitoring took place in real time and displayed in the form of data tables and graphs. The data information of the PV system comes from the sensors connected to the Arduino device which then connected to a PC. Furthermore, data recorded using Visual Basic.Net software converted into Microsoft Excel so it can be analysed further. The PV system performance analysis consists of the synchronisation process, power curve and electrical energy that can be generated by a rooftop PV system. The average solar panels start generating electricity from 7:00 am to 6:00 pm for sunny weather, but for rainy weather, the power of the PV goes down and disconnects early before sunset. The results presented show that the performance of PV systems connected to the PLN network is highly dependent on weather conditions. The monitoring result of power and energy potency can be used as a consideration parameter for a feasibility study of rooftop PV system installed in the tropical area.